Orosomucoid Proteins Interact with the Small Subunit of Serine Palmitoyltransferase and Contribute to Sphingolipid Homeostasis and Stress Responses in Arabidopsis - Li, Jian (Plant Cell, 2016)
Serine palmitoyltransferase (SPT), a pyridoxyl-5′-phosphate-dependent enzyme, catalyzes the first and rate-limiting step in sphingolipid biosynthesis. In humans and yeast, orosomucoid proteins (ORMs) negatively regulate SPT and thus play an important role in maintaining sphingolipid levels. Despite the importance of sphingoid intermediates as bioactive molecules, the regulation of sphingolipid biosynthesis through SPT is not well understood in plants. Here, we identified and characterized the Arabidopsis thaliana ORMs, ORM1 and ORM2. Loss of function of both ORM1 and ORM2 (orm1 amiR-ORM2) stimulated de novo sphingolipid biosynthesis, leading to strong sphingolipid accumulation, especially of long-chain bases and ceramides. Yeast two-hybrid, bimolecular fluorescence complementation, and coimmunoprecipitation assays confirmed that ORM1 and ORM2 physically interact with the small subunit of SPT (ssSPT), indicating that ORMs inhibit ssSPT function. We found that orm1 amiR-ORM2 plants exhibited an early-senescence phenotype accompanied by H(2)O(2) production at the cell wall and in mitochondria, active vesicular trafficking, and formation of cell wall appositions. Strikingly, the orm1 amiR-ORM2 plants showed increased expression of genes related to endoplasmic reticulum stress and defenses and also had enhanced resistance to oxidative stress and pathogen infection. Taken together, our findings indicate that ORMs interact with SPT to regulate sphingolipid homeostasis and play a pivotal role in environmental stress tolerance in plants.